2021
DOI: 10.3389/fmicb.2021.747606
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Plasmid DNA Into Bacterial Membrane Vesicles by Peptidoglycan Defects in Escherichia coli

Abstract: Membrane vesicles (MVs) are released by various prokaryotes and play a role in the delivery of various cell-cell interaction factors. Recent studies have determined that these vesicles are capable of functioning as mediators of horizontal gene transfer. Outer membrane vesicles (OMVs) are a type of MV that is released by Gram-negative bacteria and primarily composed of outer membrane and periplasm components; however, it remains largely unknown why DNA is contained within OMVs. Our study aimed to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“… 12 demonstrated, for the first time, the association of DNA with MVs released by Gram-positive bacteria belonging to the Ruminococcus genus, and the capability of these MVs to restore a specific metabolic activity in mutant strains 12 . Moreover, MVs have been reported to transfer plasmids between different strains 13 , 14 and DNA cargo into eukaryotic host cells 15 .…”
Section: Introductionmentioning
confidence: 99%
“… 12 demonstrated, for the first time, the association of DNA with MVs released by Gram-positive bacteria belonging to the Ruminococcus genus, and the capability of these MVs to restore a specific metabolic activity in mutant strains 12 . Moreover, MVs have been reported to transfer plasmids between different strains 13 , 14 and DNA cargo into eukaryotic host cells 15 .…”
Section: Introductionmentioning
confidence: 99%
“…in bacterial OMVs remained largely unexplained [ 20 , 34 , 38 , 75 ]. There are very few studies on how nucleic acids and cytoplasmic proteins pass through the bacterial inner membrane and are packaged into OMVs [ 76 ] ( Fig 15A ). It is possible that cytoplasm-carrying vesicles are not bona fide OMVs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to short term resistance, we now have reason to believe that MVs promote the development of long-term adaptive resistance to antibiotics via the horizontal transfer of resistance genes. Recently, it was reported that glycine induced peptidoglycan defects in E. coli caused the bacteria to secrete MVs which carried plasmid DNA ( Aktar et al, 2021 ). Though the peptidoglycan defects described in this paper arose from glycine, these findings beg the question: do antibiotics or other environmental influences which impact the peptidoglycan layer also favor the production of plasmid carrying MVs?…”
Section: Membrane Vesicles As An Adaptation To Environmental Insults ...mentioning
confidence: 99%